Pengaruh Kualitas Pelayanan, Harga Terhadap Loyalitas Konsumen Dan Kepuasan Konsumen Sebagai Variabel Intervening Pada Perusahaan Jasa Pengiriman Di Solo - Rustam Aji, Sidiq; , Muzakar Isa SE., M.Si (2017)
This research is used to analyze the influence of service quality, and price to consumer loyalty and consumer satisfaction as intervening variable at Service Delivery Company in Solo. Data were collected by using questioner and the sample was 100 respondents. Testing is done with SPSS Software analysis tools and methods used regression analysis and data instrument. The findings indicate that the quality of service and the significant price beperngaruh to consumer satisfaction. And consumer satisfaction mediate between service quality and price significantly influence to Consumer Loyalty